Review of management of incidents involving exposure to blood in a London teaching hospital, 1989-91. Issue 6832 (11th April 1992) - Oakley, K.; Gooch, C.; Cockcroft, A.
Abstract : OBJECTIVE–To review management of incidents involving exposure to blood reported to an occupational health unit. DESIGN–Analysis of all reported incidents from January 1989 to June 1991. SETTING–London teaching hospital. SUBJECTS–447 health care workers and students. MAIN OUTCOME MEASURES–Immunisation against hepatitis B virus before exposure, proportion of known source patients tested for hepatitis B surface antigen and HIV antibodies, and reasons for not testing known source patients. RESULTS–447 incidents were reported: 337 sharps injuries and 110 other exposures. 310 staff reporting incidents (205 (82%) nurses) were already immune to hepatitis B virus, nearly always because of immunisation. 345 source patients were identified, 77 of whom had already been tested for hepatitis B surface antigen (28 positive results) and 58 for HIV antibodies (18 positive results). Of those not previously tested, 145 of 266 were subsequently tested for hepatitis B surface antigen (two positive) and 149 of 287 for HIV antibodies (none positive). The main reasons for not testing source patients were that the incident was not considered a risk, that the patient had gone home, and that the clinical team were unwilling to ask the patient. Specific hepatitis B immunoglobulin was given to 18 staff who were not immune and was avoided in 11 cases by a negative result for the patient. Prophylactic zidovudine was discussed but not given to any staff member. CONCLUSIONS–Management of exposure to blood is improved by widespread immunisation against hepatitis B virus and by knowledge of source patients' hepatitis B virus and HIV status.